Thematic Review of the Royal Hunt on the Sassanid Silver Plates: Emphasizing the Roundabout of the King's Head - Marziyeh Basiri Zadeh; Faranak Kabiri; Abdurahman Adisaputera; Muhammad Ridwan (BIRCU, 2020)
Metalworking is among the arts that have been considered for its unique features throughout history. Perhaps one of the most important reasons for using it a lot is its stamina and more durability than other materials. Another thing to consider about this is technology and the use of metals, which Iran has a valuable background in this regard. Lorestan bronze are a prominent example of this. One of the most important periods in the use of metals is the Sassanid era, during which the period of art also flourishes. Sassanid art can be considered an important part of Iran and even the world. This art period is a bridge between pre-Islamic and post-Islamic periods in Iran. During the Sassanid Empire in Iran, many silver dishes have been made in Iran, some of which has still been remained. Many of these containers are made of precious metals to symbolize strength and credibility. One of the most important drawings used in these containers is the picture of hunting and its role and related topics. Hunting in the pre-Islamic era was one of the best works and honors of the kings, because one more thing in Sassanid art is the attempt to show the holiness and authority of the kings of this era; which has been shown in the use of designs such as the roundabout of the king's head or magnifying the king's image. In this paper, by presenting examples of silver Plates that includes the role of hunting of kings, it has been tried to introduce and examine these cases.